Corporate social responsibility in Zimbabwe: Emerging trends in the financial services sector (2009-2013). - Maliki, Harton (Midlands State University, 2017)
This study focused on the emerging trends in Corporate Social Responsibility (CSR) within the financial services sector of Zimbabwe. Having noticed the continued decrease of the stakeholder image of the sector despite the relative growth and participation of this sector in the economic development, the researcher sought to unravel specific CSR activities that banks were partaking. The Zimbabwean banks have been accused of levying exorbitant charges on the poor client base, abusing customer deposits, failure to comply with the indigenization laws, failure to support the land reform with agricultural finance, failure to support the youth empowerment programmes, and poor market confidence as shown an estimated USD7,4 billion circulating in the informal sector. Whilst various scholars have attributed these to legacy issues of the pre-dollarization era, this study contends that the practice or lack thereof CSR is a key variable in the Banks regaining stakeholder confidence especially during the period 2009 to 2013 when the economy experienced relative stability. In this regard the study identified the activities, practices and policies of CSR evident in the Zimbabwe financial services sector and placed these within the development agenda of the country. Having identified these, the study analyzed the motivations for the type and level of CSR activity adopted. The study further assessed the existence of regulatory framework in Zimbabwe which would guide the practice, reporting and monitoring of the CSR activities. To achieve the above objectives, the study explored the literature on CSR where it noted the various schools of thought from the minimalist perception of Friedman (1970) that advocated that corporates should only focus on profit making, to the broad stakeholder school led by Carrol (1979) which have been further refined (Buchholtz & Carroll, 2009) to articulate that corporates have economic, legal, ethical and philanthropic responsibilities to the ‘public’. The research applied the broader and inclusive school of CSR to the financial services sector. The researcher placed the broad CSR concept with the international, regional and national perspectives which identified standards and best practice on reporting, legislation, disclosure, employee engagement and budget spend. Questionnaires, interviews and secondary sources were used on the sampled banks in Zimbabwe with an 80% response rate that enabled generalization of the research findings. The research noted uncoordinated application of CSR in the sector, absence of consolidated legislation to drive consistency in the reporting, disclosure and financial allocation of CSR activities. There is no platform in the sector for sharing best practice and there is no senior leadership participation at Board level in the oversight and design of the CSR strategy. The research recommends the adoption of legislation which would guide the implementation of the CSR agenda, setting up of CSR Board Committee composed on independent non-executive directors and setting up a platform at Bankers Association of Zimbabwe to migrate and share best practice in the industry. The study recommends further studies on CSR within the financial services sector to assess the level of integration of CSR within the corporate strategy. Furthermore the study should aim to make recommendations on the guidelines/framework that can be used by organization to integrate CSR into the strategy.